LES INTERFERENCES LEXICALES ET MORPHOLEXICALES DANS LES PRODUCTIONS ORALES ET ECRITES DES ELEVES DE QUELQUES ECOLES SECONDAIRES DE LA VILLE DE KISANGANI - Jacques MUKONKOLE Lukombe, (IJRDO- Journal of Educational Research, 2022)
This article was born from the observation that students borrow from national languages, including Kiswahili and Lingala, certain lexemes that they introduce in French during their conversations or other public speaking. This situation results from the lack of appropriate vocabulary in their lexical background. They then resort to certain words of their own invention or jargon to compensate for this lexical deficiency. These words used therefore come from the neologism or derivation or borrowing, from the processes of lexical creation. Other words, although existing, are misused out of ignorance or confusion.